Stent-induced neutrophil activation is associated with an oxidative burst in the inflammatory process, leading to neointimal thickening - Inoue, Teruo; Kato, Toru; Hikichi, Yutaka; Hashimoto, Shigemasa; Hirase, Tetsuaki; Morooka, Toshifumi; Imoto, Yoshitaka; Takeda, Yuji; Sendo, Fujiro; Node, Koichi (Thrombosis and Haemostasis, 2006)
Activation of leukocytes plays an essential role in the mechanism of restenosis. Prior research has focused on monocytes and little is known about the role of neutrophils in this process. Neutrophils are known to contribute to tissue injury through oxygen-derived free radicals that nitrate tyrosine. This study was designed to elucidate clinically the role of neutrophil-mediated oxidative burst in the regulation of the post-stent inflammatory process. In 36 patients undergoing coronary stenting, we serially measured serum levels of glycosyl-phosphatidil-inositol-anchored protein (GPI)-80, a modulator of Mac-1 on the surface of neutrophils, in samples of coronary sinus as well as peripheral blood. We also simultaneously measured the serum 3-nitrotyrosine/tyrosine ratio as an index of oxidative stress. The GPI-80 level and the 3-nitrotyrosine/tyrosine ratio increased in the coronary sinus after coronary stenting in a time-dependent manner; with the maximum increase of GPI-80 level (3.1±2.9 to 8.6±4.3 ng/ml, P<0.01) at 48 hours, and 3-nitrotyrosine/tyrosine ratio at 24 hrs (5.2±4.8 to 28.4±13.2 ×10−4, P<0.01), more strikingly than in the peripheral blood. In the coronary sinus blood, the 3-nitrotyrosine/tyrosine ratio was correlated with GPI-80 levels at 24 hr (R=0.58, P<0. 001) and at 48 hr (R=0.41, P<0.01). Multiple regressions analysis showed that the maximum responses of GPI-80 level and 3-nitrotyrosine/tyrosine ratio were independent predictors of angiographic late lumen loss. Our results may supporta hypothesis that Mac-1-dependent activation of neutrophils causes oxidative burst in the post-stent inflammatory process, possibly leading to restenosis.
Keywords: Neutrophil; Mac-1; GPI-80; nitrotyrosine; restenosis